Maximizing the positive and minimizing the negative: Social media data to study youth mental health with informed consent - Leightley, Daniel; Bye, Amanda; Carter, Ben; Trevillion, Kylee; Branthonne-Foster, Stella; Liakata, Maria; Wood, Anthony; Ougrin, Dennis; Orben, Amy; Ford, Tamsin; Dutta, Rina (Frontiers in Psychiatry, 2023)
Social media usage impacts upon the mental health and wellbeing of young people, yet there is not enough evidence to determine who is affected, how and to what extent. While it has widened and strengthened communication networks for many, the dangers posed to at-risk youth are serious. Social media data offers unique insights into the minute details of a user’s online life. Timely consented access to data could offer many opportunities to transform understanding of its effects on mental well-being in different contexts. However, limited data access by researchers is preventing such advances from being made. Our multidisciplinary authorship includes a lived experience adviser, academic and practising psychiatrists, and academic psychology, as well as computational, statistical, and qualitative researchers. In this Perspective article, we propose a framework to support secure and confidential access to social media platform data for research to make progress towards better public mental health.